PENERAPAN REGRESI COX PROPORTIONAL HAZARD PADA KEJADIAN BERSAMA (TIES) DENGAN METODE BRESLOW, EFRON, DAN EXACT - Zega, Nesty Novita Sari; Mustafid, Mustafid; Wuryandari, Triastuti (Jurnal Gaussian, 2023)
Dengue Hemorrhagic Fever (DHF) is a contagious disease that continues to be public health concern. This disease can cause death in a short time and often causes an epidemic. Semarang city has a high number of deaths due to DHF. Reducing the mortality rate due to DHF can be done by knowing the factors that affect the patient's recovery rate. Cox proportional hazard regression is a method of survival analysis that represents the relationship between the independent variable and the dependent variable in the form of survival time. This study examined hospitalized DHF patients at RSI Sultan Agung Semarang. The data contains ties, so parameter estimation is carried out using the Breslow, Efron, and Exact methods. These three methods have different levels of computational intensity and size of data ties, so these three methods will be used in this study to determine the most appropriate method for handling DHF data ties at RSI Sultan Agung Semarang. the analysis reveals that the Cox proportional hazards regression model with the Exact method is the most suitable method for handling ties and the recovery rate of DHF patients is affected by age, platelets, and hemoglobin category.